The Effect of Cardiac Diet Counseling on Knowledge of Heart Diet in Congestive Heart Failure (CHF) Patients at Prof.Dr.H Aloei Saboe Hospital, Gorontalo City - Fadli Syamsuddin; Asni Ayuba; Nurfitriah I. Nasir (Journal of Community Health Provision, 2022)
Congestive Heart Failure (CHF) is a condition in which the heart fails to pump blood to meet the needs of the body's cells for adequate nutrition and oxygen, so a special cardiac diet is required in patient care. The design of this study used pre-experimental designs one group pretest-posttest, sampling using purposive sampling, obtained 25 respondents, then given cardiac diet counseling. The results showed that the p value was 0.000 (p <0.05), which means that there is a significant effect. It can be concluded that there is an effect of cardiac diet counseling on knowledge of cardiac diet in patients with Congestive Heart Failure (CHF). So it is hoped that cardiac dietary counseling should be given to increase knowledge of cardiac diet in CHF patients, both those undergoing intensive care and outpatient care at the cardiac polyclinic.